Impact of E-Service Quality and Customer Value on Customer Satisfaction in LocalBrand - Candra, Sevenpri; Juliani, Mita (Binus Business Review, 2018)
This research aimed to investigate the impact of e-service quality and customer value on customer satisfaction. This research was descriptive-associative in which researcher described not only the value of research variables but also the influence or relationship between independent variables and the dependent variable. A survey on e-marketplace of online fashion local brand in Indonesia was conducted. Using purposive sampling, the researcher distributed questionnaires to buyers or customers on the LocalBrand (LB) website, and 150 questionnaires were analyzed. Partial Least Square (PLS) was used as the statistic method for analyzing the research model. The results show that customer value has a significant influence on the customer satisfaction. However, e-service quality does not have a significant influence on customer satisfaction.